2013
DOI: 10.1002/lary.23697
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal transpterygoid approaches: Anatomical landmarks for planning the surgical corridor

Abstract: Our novel classification and landmarks system helps to understand the anatomy of this complex area and to accurately plan the EETA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 43 publications
4
106
0
12
Order By: Relevance
“…ESS‐assisted pterygoid process approach was recommended due to the challenges posed by the presence of closely situated vital structures such as the optic nerve and the carotid artery . Although one study has suggested that endonasal pterygoid process approach could take advantage of the vidian nerve to locate the position of foramen lacerum of the internal carotid artery, another study has set up a classification to help to understand anatomy of pterygoid area to achieve endoscopic endonasal transpterygoid approach . In this study, 9 tumors were found to break through the sphenoid sinus septum and invade bilateral sphenoid sinus (stage 3, Supporting Information Suppl.…”
Section: Discussionmentioning
confidence: 79%
“…ESS‐assisted pterygoid process approach was recommended due to the challenges posed by the presence of closely situated vital structures such as the optic nerve and the carotid artery . Although one study has suggested that endonasal pterygoid process approach could take advantage of the vidian nerve to locate the position of foramen lacerum of the internal carotid artery, another study has set up a classification to help to understand anatomy of pterygoid area to achieve endoscopic endonasal transpterygoid approach . In this study, 9 tumors were found to break through the sphenoid sinus septum and invade bilateral sphenoid sinus (stage 3, Supporting Information Suppl.…”
Section: Discussionmentioning
confidence: 79%
“…2. Removal of the pterygoid processes 23 and musculature; this step grants access to the infratemporal fossa. 3.…”
Section: Surgical Approachmentioning
confidence: 99%
“…For example, the transpterygoid approach has emerged as an effective corridor to the foramen lacerum, the petrous internal carotid artery, Meckel's cave, the cavernous sinus, and the infratemporal fossa. 18 To date, however, few reports exist on endonasal resection of chondrosarcomas. Chondrosarcomas frequently comingle with chordomas, and previous reports of the use of endoscopic endonasal resection have included only 1-2 patients in whom chondrosarcoma was diagnosed.…”
Section: Illustrative Casementioning
confidence: 99%